Ulcerated lesion of the cecum as a form of presentation of gastrointestinal tuberculosis. - Loureiro, Ana Isabel (2011)
In recent years there has been an increase in the number of cases of intestinal tuberculosis mainly due to the HIV epidemic. Its clinical manifestations and endoscopic findings are nonspecific, making diagnosis difficult, requiring high degree of suspicion. The authors present the case of a man, 55 years old, immunocompetent, who goes to the doctor due to constitutional symptoms after two months of evolution. Given the family history of colon cancer, colonoscopy is sought, showing an ulcerated lesion at the blind. Histology showed non-caseating granulomas and for AFB was negative. The following study carried out with TC chest, sputum and bronchoscopy, has lead to the diagnosis of pulmonary tuberculosis with achievement of the digestive tract. The purpose of this case history is to emphasize the importance of differential diagnosis with other pathologies with similar clinical symptoms and endoscopic changes, and the role of bronchoscopy in diagnosis of pulmonary tuberculosis in patients with negative smear.